ASPECTS THAT SHAPE THE MIDWIVE’ PERCEPTION OF VAGINAL BIRTH AFTER CAESAREAN (VBAC) - Nurrahmi Zullianti; Dwi Izzati Budiono; adityawarman adityawarman; Pudji Lestari (UNIVERSITAS AIRLANGGA, 2022)
Background: A dramatic increase in caesarean section has occurred throughout the world, especially in developing and developed countries over the last few decades and has led to increased research, debate and concern among health professionals, governments, policy makers, scientists and clinicians so as to overcome the increase in the number of cesarean sections. then developed the technique Vaginal Birth After Caesarean Section (VBAC), namely vaginal delivery in pregnant women who have had a history of cesarean section in previous pregnancies. As the philosophy of midwifery care, namely pregnancy is a natural process and prioritizes the continuity of service that is centered on women and families, and respects the right of pregnant women to participate and gain knowledge or experience related to their pregnancy, this study aims to determine the perceptions of midwives towards Vaginal Birth After Caesarean-section (VBAC). Methods: This study used a qualitative research design using a phenomenological approach and with in-depth interviews with 6 respondents who were midwives at Puskesmas Benowo. Results:The results obtained in this study are that there are five aspects that influence the perception of midwives regarding VBAC which can indeed be done but with many considerations and all of them are carried out according to applicable regulations which in Puskesmas Benowo use KSPR and it is known that pregnant women with a history of SC have a high score who must get a planned early referral. Conclusion:The conclusion of this study, there are limitations of midwives in knowledge and authority to mothers with a history of CS and also about Vaginal Birth After Caesarean-section (VBAC), but midwives still provide education and motivation to mothers to prepare for pregnancy and childbirth as well as possible for The goal is to get a healthy mother and baby.